The film medium as an educational tool - Garrido Parrilla, Joaquín David (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Throughout history, cinema has developed a variety of social functions beyond its playful, entertainment-based facet. These functions include its capacity to record fundamental historical events, its great effectiveness as a tool for publicity or propaganda, its ability to interact with other artistic disciplines, its capacity to educate and raise awareness in society, its ethical or philosophical capacity and its informative facet.